Climate policies after Paris: Pledge, trade, and recycle. Insights from the 36th Energy Modeling Forum study (EMF36) - Christoph Böhringer; Sonja Peterson; Thomas F. Rutherford; Jan Schneider; Malte Winkler (Kiel Institute for the World Economy (IfW), 2021)
This article summarizes insights of the 36th Energy Modeling Forum study (EMF36) on the magnitude and distribution of economic adjustment costs to greenhouse gas emission reduction targets. Under the Paris Agreement countries voluntarily committed themselves to emission reductions - so-called Nationally Determined Contributions (NDCs) - in order to combat global warming. The study suggests that tightening of NDCs in line with the commonly agreed 2 degrees temperature target will induce global economic costs of roughly 1% in 2030 - yet, these costs are unevenly spread across regions with fossil fuel exporting countries being most adversely affected from the transition towards a low-carbon economy. In order to reduce adjustment costs at the global and regional level, comprehensive emissions trading which exploits leastcost abatement options is strongly desirable as it can relax contentious normative debates on equitable burden sharing. Lump-sum recycling of revenues from emissions pricing in equal amounts to every household appeals as an attractive strategy to mitigate regressive effects and thereby make stringent climate policy more acceptable on societal fairness grounds.
Keywords: D58; H23; Q54; Q58; 330; Paris Agreement; emissions pricing and trading; revenue recycling